Comparison of maternal and neonatal morbidity in transvaginal versus transabdominal cerclage patients: A retrospective study from two tertiary hospitals - JinBo Li; HongYe Jiang; ShuZhong Yao; ShuQin Chen (Elsevier, 2024)
Objective: To compare the maternal and neonatal morbidity in patients with transvaginal (TVC) versus transabdominal (TAC) cerclage. Materials and methods: Retrospective analysis of patients who received cervical cerclage and terminated the pregnancy in the second trimester or third trimester in two tertiary hospitals. Data on basic clinical characteristics, predelivery maternal morbidity, intrapartum morbidity, postpartum morbidity and neonatal morbidity of TVC patients and TAC patients were analysed and compared. Results: Seventy-two TVC patients and 120 TAC patients were included. The rates of abnormal fetal presentation and placental disorders were significantly higher in TAC patients than that in TVC patients (21.67% vs 5.56% and 18.33% vs 4.17%, respectively). The rates of premature rupture of membranes and intrauterine infection were significantly higher in TVC patients than that in TAC patients (25.00% vs 2.50% and 11.23% vs 3.33%, respectively). Compared with TVC patients, the rates of estimated intrapartum hemorrhage ≥500 ml, uterine rupture and cesarean delivery in the third trimester were significantly higher in TAC patients than in TVC patients. Gestational age at delivery and neonatal morbidity were comparable between TVC patients and TAC patients. Conclusion: Compared with TVC patients, TAC patients were associated with a significantly higher incidence of maternal morbidity in placental disorders, abnormal fetal presentation, intrapartum hemorrhage ≥500 ml and uterine rupture.